Balancing safe sport policies and training demands in elite athletic environments - Zilberman, D. (University of Western Ontario, 2025)
Safe Sport (SS) was implemented in the Canadian sport system in 2019, as a result of a series of sport conferences held across the country to eradicate all forms of abuse in sport. The Coaching Association of Canada (CAC) developed SS training for all members of sporting organizations. Furthermore, for members to be in good standing and eligible to participate in provincial and national sporting events, national sport organizations (NSO) and provincial sport organizations (PSO) require mandatory SS training and certification. SS development and implementation in elite sport was a necessity, as there were several high-profile cases of abuse, thus, raising questions about the safety of athletes in elite sport. Elite athletic performance (top eight placement at the world championships or Olympic games) is a grueling process that requires personal sacrifice, extreme training demands, physical pain and psychological stress. The coaches at the Northern Lights Club (NLC) have a 40-year history of consistently developing elite athletic performance and agree with the implementation of SS policies. The Problem of Practice being addressed in this organizational improvement plan is the challenge of balancing elite athletic development while adhering to SS policies. NLC change will be lead using a coaching style and a collaborative leadership style. Additionally, the PoP will be examined employing a PESTEL analysis, the change path model, the GROW model, the foursquare coaching framework and emotional intelligence as a mechanism to lead. Communication and monitoring and evaluation plans will additionally be discussed.